2012
DOI: 10.1002/gcc.21970
|View full text |Cite
|
Sign up to set email alerts
|

Several mechanisms lead to the inactivation of the CDKN2A (P16), P14ARF, or CDKN2B (P15) genes in the GCB and ABC molecular DLBCL subtypes

Abstract: Diffuse large B-cell lymphoma (DLBCL) represents the most frequent type of aggressive lymphoma. Deletions of the CDKN2A locus, encoding the proteins CDKN2A (P16), P14ARF, and of the CDKN2B locus, encoding the protein CDKN2B (P15), affect one-third of DLBCL patients. Although other mechanisms that decrease gene expression have been reported, such as promoter methylation, the prognostic value of these mechanisms is still unclear. We studied the deletion and methylation status of these genes in 171 patients and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…The genomic complexity of RS was intermediate to that of CLL and DLBCL 38 ; RS patients with inactivation of TP53 and/or CDKN2A experienced shorter survival than RS patients without these defects, a finding consistent with the poor prognosis associated with CDKN2A loss in de novo DLBCL. [39][40][41] In another recent article, Fabbri and colleagues reported similar observations using whole-exome sequencing to compare the CLL and RS phases of 9 patients with RS. 42 Potential epigenetic events contributing to the pathogenesis of RS in CLL patients have also been explored.…”
Section: Somatic Genetic Characteristicsmentioning
confidence: 62%
“…The genomic complexity of RS was intermediate to that of CLL and DLBCL 38 ; RS patients with inactivation of TP53 and/or CDKN2A experienced shorter survival than RS patients without these defects, a finding consistent with the poor prognosis associated with CDKN2A loss in de novo DLBCL. [39][40][41] In another recent article, Fabbri and colleagues reported similar observations using whole-exome sequencing to compare the CLL and RS phases of 9 patients with RS. 42 Potential epigenetic events contributing to the pathogenesis of RS in CLL patients have also been explored.…”
Section: Somatic Genetic Characteristicsmentioning
confidence: 62%
“…Importantly, in DLBCL, CDKN2A losses have been associated with a poor outcome and with a non2GCB-phenotype. 16,31,32 In addition, there are previous suggestions of the importance of cell-cycle deregulation in RS. 30,[33][34][35] In our RS series, CDKN2A losses also were associated with poor outcome and occurred mostly concomitantly with TP53 inactivation.…”
Section: Discussionmentioning
confidence: 99%
“…[32][33][34] In addition to histone modifiers and small noncoding RNAs, chemical modifications of DNA such as cytosine methylation emerged recently as paramount in regulating genome stability and gene expression. Targeted studies identified several loci with altered DNA methylation in DLBCL, including INK4A, 35,36 MGMT, 37,38 and BCL6. 39 Following these observations, we asked whether such changes are widespread in the genome of DLBCL .…”
Section: Discussionmentioning
confidence: 99%
“…This appears to be a progressive oncogenic event that is more common in more aggressive DLBCLs (clusters E and F). Prior reports highlighted frequent deletion of the INK4B-ARF-INK4A locus in patients with DLBCLs 35,36,50,51 and suggested that an alternative mechanism of gene inactivation through aberrant hypermethylation also exists and cumulatively with deletions may affect between one-third and one-half of patients with DLBCLs. In addition, we demonstrated aberrant hypermethylation of CDKN1A and CDKN1B, which is a novel finding.…”
Section: Discussionmentioning
confidence: 99%